Navigating Existence and Community Harmony: A Case Study of Pondok Pesantren in Muslim Minority Ende, Nusa Tenggara Timur - Sabarudin, Sabarudin; Mubin, Muhammad Nurul; Maghfuri, Amin; Achadi, Muh. Wasith; Mardeli, Mardeli; Syarnubi, Syarnubi; Widodo, Sembodo Ardi (SCAD Independent, 2024)
This study examines Pondok Pesantren Wali Sanga Gunung Meja’s strategies to thrive within a Catholic-majority community in Ende, Nusa Tenggara Timur, emphasizing interfaith harmony and educational resilience. This study employs a qualitative case study approach to delve into the institution’s adaptive methods and contributions to communal harmony. It does so through semi-structured interviews, non-participant observations, and document analysis. Results highlight the institution’s ability to foster mutual respect and social cohesion through various programs grounded in its foundation of collaboration between Islamic and Catholic figures. The study identifies critical factors for its sustainability: fostering Silahturahmi (communication and friendship), collaboration with the Catholic community, and commitments to social-cultural integration, education, and self-reliance. These elements collectively enhance the Pesantren’s role in promoting religious understanding and community harmony. The findings suggest that Pesantren’s approach offers a model for navigating religious identity complexities and community integration. Limitations include the study’s focus on a single institution and reliance on qualitative data, pointing to the need for broader comparative research to generalize findings. The study underscores the potential of religious education in advancing social harmony, advocating for further exploration across diverse settings.